Komunikasi Organisasi antara Kepala Gudang dan Staf PT. Pertiwimas Adi Kencana di Masa Pandemi Covid-19 - Ivan Putra Harnandika; Yenni Yenni (Universitas Merdeka Malang, 2022)
The Covid-19 pandemic is spreading around the world The World Health Organization (WHO) has designated this as a pandemic caused by the increasing number of cases. The Covid-19 pandemic that spreads in various countries in the world also affects various aspects of human life, one of which is for Indonesia. The increasing number of Covid-19 cases in Indonesia finally made the Government set a policy by implementing Large-Scale Social Restrictions (PSBB). Large-Scale Social Restrictions Efforts were taken in order to break the spread of Covid-19 which has caused economic losses which resulted in the company terminating its employees due to the unstable condition of the company. These conditions forced the company to turn around in difficult times during the Covid-19 pandemic, one of which was PT. PERTIWIMAS ADI KENCANA. This study aims to determine organizational communication between the Head of Warehouse and Staff of PT. PERTIWIMAS ADI KENCANA during the Covid-19 pandemic. This research is a descriptive qualitative research that uses data collection techniques using interviews. The findings in this study indicate that vertical communication dominates organizational communication between the Head of the Warehouse and the staff of PT. PERTIWIMAS ADI KENCANA during the Covid-19 pandemic. It is this type of communication that distinguishes upward and downward vertical communication. Direct communication dominates vertical downward communication, while indirect communication dominates vertical upward communication.Keywords: Organizational Communication; Head of Warehouse; Staff; PT. Pertiwimas Adi Kencana; Covid-19 Pandemic.